Antiretroviral Drug Use in a Cross-Sectional Population Survey in Africa: NIMH Project Accept (HPTN 043) - Fogel, Jessica M; Clarke, William; Kulich, Michal; Piwowar-Manning, Estelle; Breaud, Autumn; Olson, Matthew T; Marzinke, Mark A; Laeyendecker, Oliver; Fiamma, Agnès; Donnell, Deborah; Mbwambo, Jessie K K; Richter, Linda; et al. (Journal of acquired immune deficiency syndromes (1999), 2017)
BACKGROUND: Antiretroviral (ARV) drug treatment benefits the treated individual and can prevent HIV transmission. We assessed ARV drug use in a community-randomized trial that evaluated the impact of behavioral interventions on HIV incidence. METHODS: Samples were collected in a cross-sectional survey after a 3-year intervention period. ARV drug testing was performed using samples from HIV-infected adults at 4 study sites (Zimbabwe; Tanzania; KwaZulu-Natal and Soweto, South Africa; survey period 2009-2011) using an assay that detects 20 ARV drugs (6 nucleoside/nucleotide reverse transcriptase inhibitors, 3 nonnucleoside reverse transcriptase inhibitors, and 9 protease inhibitors; maraviroc; raltegravir). RESULTS: ARV drugs were detected in 2011 (27.4%) of 7347 samples; 88.1% had 1 nonnucleoside reverse transcriptase inhibitors ± 1-2 nucleoside/nucleotide reverse transcriptase inhibitors. ARV drug detection was associated with sex (women>men), pregnancy, older age (>24 years), and study site (P < 0.0001 for all 4 variables). ARV drugs were also more frequently detected in adults who were widowed (P = 0.006) or unemployed (P = 0.02). ARV drug use was more frequent in intervention versus control communities early in the survey (P = 0.01), with a significant increase in control (P = 0.004) but not in intervention communities during the survey period. In KwaZulu-Natal, a 1% increase in ARV drug use was associated with a 0.14% absolute decrease in HIV incidence (P = 0.018). CONCLUSIONS: This study used an objective, biomedical approach to assess ARV drug use on a population level. This analysis identified factors associated with ARV drug use and provided information on ARV drug use over time. ARV drug use was associated with lower HIV incidence at 1 study site.
Keywords: National Institute of Mental Health (U.S.); Spojené státy americké; Pregnancy; Humans; Anti-Retroviral Agents; HIV infekce; HIV Infections; Female; antiretrovirové látky; mladý dospělý; dospělí; Národní institut pro duševní zdraví (USA); lidé; spotřeba léčiv; United States; randomizované kontrolované studie jako téma; Africa; Adult; ženské pohlaví; Male; Randomized Controlled Trials as Topic; Afrika; Retrospective Studies; Adolescent; těhotenství; Cross-Sectional Studies; Young Adult; Drug Utilization; retrospektivní studie; mužské pohlaví; průřezové studie; mladiství